A Psycho-pedagogic Approach for Inclusive Classes in Disadvantaged Rural Primary Schools in South Africa:Advancing Teaching Practices. (1st January 2016) - Buka, Andrea Mqondiso; Molepo, Jacob Maisha
Abstract: This paper focuses on pedagogic processes and dilemmas faced by teachers in inclusive classes with diverse learning barriers in South Africa. It also aimed at strengthening teaching practices and learning-support strategies (TPLSSs) which teachers use in inclusive classes (ICs) in disadvantaged, rural primary schools. There were 19 teachers, including inclusive classroom caregivers (ICCs) in 13 schools (n = 19, mean age = 45, males = 2, females = 17) who participated. A qualitative mode of inquiry was used together with a case-study approach as the research design. Data were thematically analyzed and revealed that learners experiencing barriers to learning (LEBTLs) were still marginalized and minimally-supported in the classroom context while teachers used unsuitable pedagogic approaches which were an indication of inadequate lesson planning. A pedagogic-inclusive approach was developed from the project and called the Triad Pedagogic Perspective (TPP) model.